Toxoplasma gondii infection by serological and molecular methods in schizophrenia patients with and without suicide attempts: An age‐sex‐matched case‐control study. Issue 8 (16th June 2021) - Akgül, Özer; Demirel, Ömer Faruk; Aksoy Poyraz, Cana; Tanriöver Aydin, Ezgi; Uysal, Nuray; Bulu, Ersel; Sapmaz, Burcu; Çalişkan, Reyhan; Öner, Yaşar Ali
Abstract: Introduction: The opinion that latent Toxoplasma gondii infection is having a broadly asymptomatic projection has now been interrogated, in specific due to the echoed association between the latent infection and an elevated incidence of schizophrenia or even suicide attempts. Notwithstanding conducted studies aimed to understand this feasible link are restricted. Methods: In the present case‐control study, we focused to illuminate the relationship between the serological and molecular presence of T gondii and schizophrenia with or without the suicide attempts by comparing it with healthy individuals. A total of 237 participants (117 in schizophrenia and 120 in healthy control) were included in this study. Results: Overall, latent T gondii infections were found statistically higher in 63 (53.8%) of the 117 patients with schizophrenia and in 33 (27.5%) of the 120 controls ( P < .001). In schizophrenia patients, seroprevalence T gondii was again found to be statistically higher in suicide attempters (59.6%), compared with no history of suicide attempts (48.3%; P < .05). The molecular positivity rate of T gondii DNA was higher in the schizophrenia group, compared with the healthy control group ( P < .05), whereas the history of suicide attempts was not statistically associated ( P = .831) with T gondii DNA positivity by polymerase chain reaction. Conclusion: This case‐control study enlightens additional demonstration to the belief that T gondii infection would be an underlying component for the pathophysiology of schizophrenia. Regardless of the clarity results of this study, this supposition warrants further endorsement.